Perancangan Pusat Mode Muslim dengan Konsep Arsitektur Kontemporer di Kelapa Gading, Jakarta Utara - Putri, Nabila Setya; Sulistiowati, Anggraeni Dyah; Kurniawan, Dody (MAESTRO, 2020)
Fashion in Indonesia is now growing along with the flow of modernization. This development makes the community as a selective society in determining their lifestyle. Lifestyle is very closely related to fashion because fashion will support one's appearance to be more attractive and become a trend center in society. Fashion products include products that can be consumed in the long run because these products are used with normal one-year usage. Fashion products include clothing, shoes, bags, accessories, etc. The potential of the Muslim fashion industry in the country to become the center of world Muslim fashion is approaching. The Minister of Industry of the Republic of Indonesia, Airlangga Hatarto, said that this potential could be achieved by looking at the development of the national Muslim industry in the development of the world's Muslim fashion industry. According to data from The State Global Islamic Economy 2018, global consumption of Muslim fashion currently reaches 270 billion US dollars and is projected to continue to increase with a growth rate of 5 percent so that in 2023 it will touch up to 361 billion US dollars. The construction of the Muslim Fashion Center in Kelapa Gading, North Jakarta became a place of appreciation for Muslim fashion designers and users to continue working and producing it domestically. To that end, the design of this object has the aim to become a Muslim Fashion Center that truly attaches importance to the aesthetic and Islamic aspects of the Muslimah. Through the design of the Muslim Fashion Center by using the theme of Contemporary Architecture design that focuses on the building that impressed the present without having to leave the Islamic side.